2019
DOI: 10.1002/ajhb.23255
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and metabolic profile of a Brazilian Amerindian group: The Xikrin (Mebengôkre)

Abstract: Objectives: The purpose of this study was to describe the metabolic and anthropometric profile of the Xikrin (Mebengôkre), an indigenous group. Methods: A total of 363 subjects (55.1% women) aged 18 years or older were evaluated. The variables analyzed were age, body weight and height, waist circumference, blood pressure, fasting blood glucose, triglyceride level, and total cholesterol level. Results: A high prevalence of obesity (36.5%) and central obesity (88.1%), mainly among women (46.9% and 96.2%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…A few studies in our review reported a low prevalence of diabetes among some indigenous populations in LatAm [55,74,82], in parallel to some previous reports [283][284][285][286] about other indigenous groups in the region and in contrast with the higher prevalence of diabetes among American Indians in the USA [287] and the First Nations in Canada [288]. However, other studies in our review and in the current literature have documented elevated diabetes prevalence or risk among indigenous and other socioeconomically disadvantaged ethnic groups [48,50,73,76,77,83,90,91,166,[289][290][291][292][293].…”
Section: Indigenous and Other Ethnic Underserved Populationssupporting
confidence: 88%
“…A few studies in our review reported a low prevalence of diabetes among some indigenous populations in LatAm [55,74,82], in parallel to some previous reports [283][284][285][286] about other indigenous groups in the region and in contrast with the higher prevalence of diabetes among American Indians in the USA [287] and the First Nations in Canada [288]. However, other studies in our review and in the current literature have documented elevated diabetes prevalence or risk among indigenous and other socioeconomically disadvantaged ethnic groups [48,50,73,76,77,83,90,91,166,[289][290][291][292][293].…”
Section: Indigenous and Other Ethnic Underserved Populationssupporting
confidence: 88%
“…The prevalences of general obesity recorded in the Araweté and Arara peoples in 2021 are also lower than those found in most indigenous peoples for whom recent data are available and are only similar to that recorded for Suyá-Khisêdjê people, Mato Grosso (5.3%) [ 12 ]. On the other hand, the high proportions of general obesity observed in 2021 for the Kararaô, Asurini do Xingu and Gavião peoples, are similar to those found in other indigenous peoples such as the Xikrin do Cateté (36.0%), Pará [ 14 ], Kaiowá, Guarani and Terena (37.0%), from Mato Grosso [ 15 ], Kaingang (33.1%), from Santa Catarina [ 15 ] and Xavante (51%), from Mato Grosso [ 13 ].…”
Section: Discussionsupporting
confidence: 63%
“…The prevalence found in the Arara people is also still lower than that described in recent years for Brazilian indigenous peoples, which ranges from 47.3% in Suyá-Khisêdjê people, Mato Grosso [ 12 ], to 85.5% in the Xavante, also from Mato Grosso [ 13 ]. On the other hand, the high prevalence of excess weight observed in the Gavião, Kararaô, Asurini do Xingu and Xikrin do Bacajá peoples are similar to those recorded in peoples such as the Xavante, Mato Grosso (85.5%) [ 13 ], Xikrin do Cateté, Pará (78.0%) [ 14 ], Kaingang, Santa Catarina (67.1%) [ 15 ], Kaiowá, Guarani, and Terena, Mato Grosso (61.3%) [ 16 ], in which the prevalence of excess weight are higher than the global average of 52.5% estimated for the Brazilian population [ 17 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Members of the Lachnospiraceae family (such as Coprococcus) were also found to be enriched among the Native American Cheyenne and Arapaho individuals from North America, which are increasingly shifting towards an industrialised lifestyle pattern 35 . Considering a recent report 36 showing increased prevalence of obesity and type 2 diabetes among the Xikrin (R), the abundance of these taxa points to a gut microbiome similar to that of urbanised populations even in an environment with minimal intake of processed foods and medication, difficult access and linguistic barriers. In an Amazonian rural Native American population, this double burden of diseases can lead to public health issues.…”
Section: Discussionmentioning
confidence: 99%